HARNESSING THE POWER OF ROSEMARY AND KALONJI SEEDS FOR HAIR HEALTH: A REVIEW - Parth B Hariyani; Vijendra Rajan; Dr.PragneshPatani (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
This review paper gives overview on Hair health as a major problem in dermatology and cosmetology, and natural therapies are gaining popularity due to their low side effects and possible usefulness. This review examines the combined benefits of rosemary (Rosmarinus officinalis) and kalonji seeds (Nigella sativa) on hair health, concentrating on their phytochemical characteristics, modes of action, and therapeutic potential. Rosemary, which contains bioactive chemicals such as rosmarinic acid, caffeic acid, and essential oils, has long been used to encourage hair growth and treat scalp disorders like dandruff. Its antioxidant and anti-inflammatory characteristics promote scalp circulation, which may aid in hair follicle stimulation and growth. Furthermore, rosemary has been shown to block the hormone DHT (Dihydrotestosterone), a crucial role in androgenetic alopecia, making it an important component in the treatment of hair loss. Kalonji seeds, known for their high thymoquinone concentration, provide numerous hair health advantages. Thymoquinone has potent antioxidant, anti-inflammatory, and antibacterial capabilities, which protect hair follicles from oxidative stress and infections that cause hair loss. Kalonji oil has also been shown to strengthen hair, enhance texture, and prevent premature graying. The synergistic effect of rosemary and kalonji seeds in hair care is a potential topic of research since they have complementary qualities that improve hair growth, strength, and general health. This review summarizes current research on these natural compounds, focusing on their potential applications in treating common hair diseases such alopecia, dandruff, and scalp infections. The findings of this analysis will open new way for more natural, effective, and accessible hair care products